2023
DOI: 10.31223/x5ch1c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from the drain: a sensor framework that captures multiple drivers of chronic coastal floods

Abstract: Tide gauge records are commonly used as proxies to detect coastal floods and project future flood frequencies. While these proxies clearly show that sea-level rise will increase the frequency of coastal flooding, tide gauges do not account for land-based sources of coastal flooding and therefore likely underestimate the current and future frequency of coastal flooding. Here we present a new sensor framework for measuring the incidence of coastal floods that captures subterranean and land-based contributions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 19 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Furthermore, several locations on the US Southeast Atlantic, and eastern Australia (Bureau of Meteorology, 2022) have offsets of just 0.15 m between one or more flood levels. This highlights the need for the development of global flood impact databases such as those that already exist for Europe (Ciavola et al., 2018; Haigh et al., 2017) and systematic collection of impact‐based thresholds defined in national and local coastal flood studies (e.g., Ezer, 2022; Gold et al., 2023; Hague et al., 2022; Smith & Juria, 2019; Thompson et al., 2019). Further investment in LiDAR surveys will also improve the coverage of DEMs with small enough vertical errors to distinguish between floods of different severities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, several locations on the US Southeast Atlantic, and eastern Australia (Bureau of Meteorology, 2022) have offsets of just 0.15 m between one or more flood levels. This highlights the need for the development of global flood impact databases such as those that already exist for Europe (Ciavola et al., 2018; Haigh et al., 2017) and systematic collection of impact‐based thresholds defined in national and local coastal flood studies (e.g., Ezer, 2022; Gold et al., 2023; Hague et al., 2022; Smith & Juria, 2019; Thompson et al., 2019). Further investment in LiDAR surveys will also improve the coverage of DEMs with small enough vertical errors to distinguish between floods of different severities.…”
Section: Discussionmentioning
confidence: 99%
“…To study coastal flood hazards, one must ascertain the water levels that pose a threat over the timescale and region of interest (Rasmussen et al., 2022; WMO, 2015). To do this, many studies define coastal flood thresholds that represent the minimum sea level associated with some specified impact (Gold et al., 2023; Hague et al., 2019; Moore & Obradovich, 2020). These can be defined by relevant government agencies (Burgos et al., 2018; Dahl et al., 2017; Karegar et al., 2017; Sweet et al., 2014; Sweet & Park, 2014), or by leveraging social or news media and local monitoring programs (Ezer, 2022; Gold et al., 2023; Hague et al., 2022, 2020, 2019; Hino et al., 2019; Moore & Obradovich, 2020; Ritman et al., 2022; Thompson et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2018). This regression model is adopted by the National Ocean Service (NOS) and is useful to derive flooding thresholds for sites without defined NWS thresholds (Gold et al., 2023). The HTF thresholds provided by NWS and NOS are different along the US coast, with the maximum difference reaching 0.31 m and the median reaching 0.11 m. Choosing the NOS thresholds everywhere leads to different HTF frequencies, but sensitivity testing showed that the conclusions we draw from our analysis hold, and hence we use NWS thresholds throughout (with the exception of Neah Bay).…”
Section: Datamentioning
confidence: 99%